Crucial role of autophagy in propofol-treated neurological diseases: a comprehensive review - Yu, Sicong; Liao, Jian; Lin, Xuezheng; Luo, Yu; Lu, Guangtao (Frontiers in Cellular Neuroscience, 2023)
Neurological disorders are the leading cause of disability and death globally.Currently, there is a significant concern about the therapeutic strategies that can offer reliable and cost-effective treatment for neurological diseases. Propofol is a widely used general intravenous anesthetic in the clinic. Emerging studies demonstrate that propofol exerts neuroprotective effects on neurological diseases and disorders, while its underlying pathogenic mechanism is not well understood. Autophagy, an important process of cell turnover in eukaryotes, has been suggested to involve in the neuroprotective properties developed by propofol. In this narrative review, we summarized the current evidence on the roles of autophagy in propofol-associated neurological diseases. This study highlighted the effect of propofol on the nervous system and the crucial roles of autophagy. According to the 21 included studies, we found that propofol was a double-edged sword for neurological disorders. Several eligible studies reported that propofol caused neuronal cell damage by regulating autophagy, leading to cognitive dysfunction and other neurological diseases, especially high concentration and dose of propofol. However, some of them have shown that in the model of existing nervous system diseases (e.g. cerebral ischemia-reperfusion injury, electroconvulsive therapy injury, cobalt chloride-induced injury, TNF-αinduced injury, and sleep deprivation-induced injury), propofol might play a neuroprotective role by regulating autophagy, thus improving the degree of nerve damage. Autophagy plays a pivotal role in the neurological system by regulating oxidative stress, inflammatory response, calcium release, and other mechanisms, which 3 may be associated with the interaction of a variety of related proteins and signal cascades. With extensive in-depth research in the future, the autophagic mechanism mediated by propofol will be fully understood, which may facilitate the feasibility of propofol in the prevention and treatment of neurological disorders.